Development of affordable steel-framed modular buildings for emergency situations (Covid-19). (June 2021) - Gatheeshgar, Perampalam; Poologanathan, Keerthan; Gunalan, Shanmuganathan; Shyha, Islam; Sherlock, Paul; Rajanayagam, Heshachanaa; Nagaratnam, Brabha
Abstract: This paper presents the development of novel affordable steel-framed modular units for construction with enhanced overall (healthcare, structural, fire, and lightweight) performance, which ideally suits for emergency response situation, such as current covid-19 pandemic. The nature of quick response and well-prepared strategies are essential to cope with the demand of quicker construction for emergency response structures and if similar situation continues or arises in the future as well. Off-site oriented modular construction is ideal to provide these requirements at very short notice for emergencies. Modular units made of steel components are a leading choice due to the exceptional strength and rigidity for lightweight construction. A new weight optimisation procedure was developed for Cold-Formed Steel (CFS) joists in varying shapes of and results show that weight for per unit length of the joists can be reduced up to 24% without compromising structural capacity. This was verified with validated Finite Element (FE) models. In order to improve the faster jointing method, a novel cut and bend intra-module connection was also introduced. In addition, strap bracing is used for the lateral stability of steel-framed modular buildings. Modular breathing panels are proposed to be employed in corner post modules as sidewalls to improve the indoor air quality and reduce the spread of disease. Based on the comprehensive assessment and numerical results conceptual design of performance improved steel-framed corner post modular unit was proposed to offer short-to-medium (in response to emergencies), as well as long-term solutions for the construction industry.